2013
DOI: 10.1007/s11886-013-0396-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Lipid Traits and Relationship to Coronary Artery Disease

Abstract: Despite the critical importance of plasma lipoproteins in the development of atherosclerosis, varying degrees of evidence surround the causal associations of lipoproteins with coronary artery disease (CAD). These causal contributions can be assessed by employing genetic variants as unbiased proxies for lipid levels. A relatively large number of low-density lipoprotein cholesterol (LDL-C) variants strongly associate with CAD, confirming the causal impact of this lipoprotein on atherosclerosis. Although not as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 87 publications
(86 reference statements)
0
9
0
3
Order By: Relevance
“…Many studies have demonstrated that LDL induces dysfunction of endothelium (Yu et al, 2013), causes vascular wall inflammation (Fenyo and Gafencu, 2013;Wang et al, 2013), promotes vasospasm (Miwa, 2003) and ischemic heart disease (Keenan and Rader, 2013). However, the underlying molecular mechanisms how LDL leads to vasospasm and ischemic cerebro-and cardiovascular diseases are not fully understood yet.…”
mentioning
confidence: 99%
“…Many studies have demonstrated that LDL induces dysfunction of endothelium (Yu et al, 2013), causes vascular wall inflammation (Fenyo and Gafencu, 2013;Wang et al, 2013), promotes vasospasm (Miwa, 2003) and ischemic heart disease (Keenan and Rader, 2013). However, the underlying molecular mechanisms how LDL leads to vasospasm and ischemic cerebro-and cardiovascular diseases are not fully understood yet.…”
mentioning
confidence: 99%
“…К настоящему времени идентифицировано множество полиморфных вариантов генов, ассоциированных с риском развития полигенных форм ИБС [11]. Наиболее выраженными эффектами в отношении риска развития болезни обладали такие гены, как PCSK9 [11][12][13][14], LPA [10], NPC1L1 [15], ST3GAL4 [16], генный кластер APOE-C1-C2-C4 [17], COBLL1 [15], LRP4 [10], STARD3 [18], ABCA1 [10,19], SCARB1 [20][21][22], CETP [23,24], PLTP [25,26], LCAT [10]. Продукты экспрессии идентифицированных генов не ограничены влияниями на липидный обмен, а вовлечены в разнообразные молекулярные механизмы развития ИБС.…”
Section: ибсunclassified
“…Ген PCSK9 -высоко полиморфный. Установлена ассоциация полиморфного варианта rs17111503 гена PCSK9 с развитием атеросклеротических поражений сосудов у китайцев [13,14]. Также показано, что носители полиморфного варианта требуют специальной тактики для коррекции уровня холестерина в крови [29].…”
Section: ибсunclassified
“…Circulating blood lipid levels are important risk factors for cardiovascular disease, and the GWAS approach has yielded numerous variants associated with lipid traits and coronary artery disease (34). A recent study has reported genotyping of the exome array (Box 1) with lipid traits (24).…”
Section: Some Case Studies In Cardiometabolic Traits Illustrating Sommentioning
confidence: 99%